2013
DOI: 10.3390/ijerph10115603
|View full text |Cite
|
Sign up to set email alerts
|

Walking for Well-Being: Are Group Walks in Certain Types of Natural Environments Better for Well-Being than Group Walks in Urban Environments?

Abstract: The benefits of walking in natural environments for well-being are increasingly understood. However, less well known are the impacts different types of natural environments have on psychological and emotional well-being. This cross-sectional study investigated whether group walks in specific types of natural environments were associated with greater psychological and emotional well-being compared to group walks in urban environments. Individuals who frequently attended a walking group once a week or more (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 79 publications
6
100
0
7
Order By: Relevance
“…In a large-scale evaluative study, Marselle et al [33] found that group walks in natural environments were associated with better mental health. Additional analyses found that group walks in farmland or green corridors were associated with a significant reduction in stress and negative emotions [35] and that elements associated with an outdoor group walk (e.g., biodiversity, naturalness, intensity, duration) affect wellbeing [36] and are mediated by the perceived restorativeness of the environment [37]. However, a major limitation of these previous works is the lack of pre-post health and wellbeing evaluations [29,33].…”
Section: Rationale For Group Walks In Naturementioning
confidence: 99%
See 1 more Smart Citation
“…In a large-scale evaluative study, Marselle et al [33] found that group walks in natural environments were associated with better mental health. Additional analyses found that group walks in farmland or green corridors were associated with a significant reduction in stress and negative emotions [35] and that elements associated with an outdoor group walk (e.g., biodiversity, naturalness, intensity, duration) affect wellbeing [36] and are mediated by the perceived restorativeness of the environment [37]. However, a major limitation of these previous works is the lack of pre-post health and wellbeing evaluations [29,33].…”
Section: Rationale For Group Walks In Naturementioning
confidence: 99%
“…Walk-related information included: date of walk (write in: date); the weekly walk number (write in: the weekly walk number, e.g., 1, 2); the number of people attending (write in: number); the duration of the walk (write in: walk start time and walk end time); and the distance walked (write in: distance including source of information about distance, e.g., estimate, phone-based app). The walk environment was measured with a list of categories (e.g., natural and semi-natural places, green corridors, public spaces) that has previously been used in nature-health research [35]. The Walk Leader was asked to select the one that 'best describes the site' in which the walk took place.…”
Section: Walk Attendance Distance Duration Natural Environsmentioning
confidence: 99%
“…This finding is buttressed by a more recent study of 708 participants that compared the effects of walking exercise in a natural environment as opposed to walking exercise in an urban environment (Marselle et al 2013). The investigators found that, group walks in farmland were significantly associated with less perceived stress, more positive mood, and greater mental wellbeing than walks in urban environments (Marselle et al 2013). They concluded that outdoor walking group programs could be endorsed through "green prescriptions" to improve psychological and emotional well-being, as well as physical activity.…”
Section: Exercise and Eco-therapies For Depressionmentioning
confidence: 45%
“…Furthermore, reduced levels of state anxiety have been reported following green exercise experiences [21] and correlations have been observed between active involvement in environmental groups and positive health, wellbeing and social connectedness [22]. A meta-analysis revealed that a walk/run in a natural environment, (e.g.…”
Section: Potential Benefits Of Green Physical Activitymentioning
confidence: 99%
“…Existing data on green PA can be interpreted to suggest that diverse affordances may offer more physical possibilities, better social interactions; positive psychological responses and emotional feelings compared to indoor environments with limited affordances. Environments with more natural features tend to be preferred and associated with more positive physical and mental health outcomes [21]. Some parameters may be stable attractors which encourage emergence of specific behaviours or may provide information for action possibilities or positive emotional feelings.…”
Section: Ecological Dynamics: a Suitable Framework For Green Physicalmentioning
confidence: 99%